A CONCEPTUAL MODEL OF TRI HITA KARANA IN EDUCATIONAL GLOCALIZATION: TOWARD ETHICAL CULTURAL COMMODIFICATION - L. Virginayoga Hignasari; Made Sutajaya; Md. Yudyantara Risadi; Putu Putri Dena Laksmi; I Wayan Budiarta; Yuni Misrahayu; Noor Akhmad; Agustinasari; Ni Komang Dwi Eka Yuliati (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2026)
This study examines the repositioning of Tri Hita Karana (THK) within the context of educational glocalization in Bali. Previous studies have predominantly treated THK as a normative and ceremonial value system, with limited attention to its potential as a strategic epistemic and educational framework. Using a qualitative conceptual approach based on documentary analysis and a critical interpretive perspective, this study aims to develop a conceptual model of THK implementation in educational glocalization and to explore how ethical cultural commodification may function as a strategy for cultural empowerment rather than mere commercialization. The study develops a three layer conceptual model consisting of: (1) a value foundation layer that positions THK as the ontological and epistemic basis of education; (2) an educational transformation layer that conceptualizes glocalization as a mechanism for integrating local values into curriculum, pedagogy, and cross-cultural learning processes; and (3) an empowerment and cultural bargaining layer that frames education as a space for cultural diplomacy, community collaboration, and ethically grounded cultural commodification. These layers are operationalized into six strategic phases, including institutional legitimation, value internalization, cross-cultural negotiation, curriculum glocalization, cultural dissemination, and value-based commodification. The findings indicate that THK can function not only as a framework for cultural preservation but also as strategic cultural capital capable of strengthening educational identity, cultural agency, and local-global negotiation within contemporary education. The study contributes a conceptual framework that repositions THK from a symbolic cultural philosophy into a dynamic educational model relevant to multicultural and globalized learning environments.